A Comprehensive Electricity Market Model Using Simulation and Optimization Techniques - Steber, David; Hübler, Jakob; Pruckner, Marco (Proceedings of 2018 Winter Simulation Conference, 2018)

Benefits of Virtual Community Energy Storages compared to Individual Batteries based on Behaviour Based Synthetic Load Profiles - Schlund, Jonas; Pflugradt, Noah; Steber, David; Muntwyler, Urs; German, Reinhard (Proceedings of the 2018 IEEE PES Innovative Smart Grid Technologies Conference Europe (ISGT Europe), 2018)
This paper focuses on a low-voltage grid area consisting of 500 distributed households with both photovoltaics and a battery. If every household focuses only on its self-consumption, the batteries run inefficiently and the grid is stressed unnecessarily. Thus, the batteries within the considered area are connected to form a virtual community energy storage. To simulate such an environment, individual and realistic load profiles for each household are needed. This paper presents a novel, behavior based load profile generator to get such profiles. It is shown that these profiles aggregate to the German standardized load profile H0. An already existing simulation model of decentralized households is adapted in order to include community controllers, which aggregate and distribute the corresponding power flows in order to run the batteries efficiently and avoid unnecessary power flows. The whole low-voltage grid area is simulated for various community sizes within the area. Utilizing community power leads to a better overall efficiency, a decrease in the workload of the grid and a higher self-sufficiency within the considered area. These benefits can already be achieved at small community sizes.<br

Combined Optimization, Simulation and Grid Analysis of the German Electrical Power System in an European Context (KOSiNeK) - Presentation of the research project and first results - Steber, David; Pruckner, Marco; Thurner, Christoph; Burlacu, Robert; Graber, Thomas; Deß, Tobias; Luther, Matthias; Martin, Alexander; German, Reinhard (Integration of Sustainable Energy Conference (ISEneC) 2018, 2018)

Ein Regionenmodell zur Herleitung der lokalen elektrischen Residuallast und thermischen Last in Deutschland - Steber, David; Hümmer, Benedikt; Gürtner, Christian; German, Reinhard; Pruckner, Marco (15. Symposium EnergieInnovation, 2018)

Hierarchical Simulation of the German Energy System and Houses with PV and Storage Systems - Bazan, Peter; Pruckner, Marco; Steber, David; German, Reinhard (Energy Informatics - 4th D-A-CH Conference, EI 2015, Karlsruhe, Germany, November 12-13, 2015, Proceedings, 2015)
The increase of renewable energies leads to new solutions in the field of decentralized energy storage. Houses with photovoltaic systems and battery storage systems can provide services for the power grid. But the isolated examination of only a few houses neglects the interaction of the houses with the power grid. We combine a model of the German energy system and a model of houses with photovoltaics and batteries. The two coupled hierarchical simulation models are then used to study different scenarios regarding the extension of renewable energy sources in Bavaria. Due to differences between the forecasted and real residual load and restrictions in the transmission grid, provision of control power is needed. The case studies show the amount of control power that will be provided by the houses with battery storage systems. In addition, the impacts on the electricity costs per year for a house are show
UnivIS-Import:2015-11-17:Pub.2015.tech.IMMD.IMMD7.hierar
Keywords: Hierarchical modeling; Electrical energy system; Renewable energy; Control power; Storage system; Model aggregation; Hybrid simulation

Hybrid simulation and energy market based optimization of cement plants - Bazan, Peter; Steber, David; German, Reinhard (Computer Science - Research and Development, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.IMMD.IMMD7.hybrid
Keywords: CO; Day-ahead electricity market; Demand side management; Frequency restoration reserve; Redox flow battery; Renewable energy sources

Including a virtual battery storage into thermal unit commitment - Steber, David; Pruckner, Marco; Schlund, Jonas; Bazan, Peter; German, Reinhard (Computer Science - Research and Development, 2017)
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD7.includ
Keywords: CO_22emissions; Distributed generation management; Energy networks; Grid integration of storage; Virtual battery storage; Virtual power plant

Increasing the Efficiency of a Virtual Battery Storage Providing Frequency Containment Reserve Power by Applying a Clustering Algorithm - Schlund, Jonas; Steber, David; Bazan, Peter; German, Reinhard (Proceedings of the 7th Innovative Smart Grid Technologies Asia, 2017)
We consider a virtual battery energy storage consisting of individual storage systems used for both, maximization of household PV-power self-consumption and provision of frequency containment reserve power. A central controller manages the frequency containment reserve power provision by setting benchmarks for each individual storage every 15 minutes. The individual storage systems provide frequency containment reserve power autonomously based on the frequency deviation to its nominal value and the given benchmark. A uniform frequency containment reserve power dispersion to all individual storage systems causes marginal power requests most of the time, which lead to high losses due to the bad efficiency of the rectifiers in low part-load operation. Therefore, this paper suggests an algorithm for only using subsets of the virtual battery energy storage with a certain amount of individual systems for frequency containment reserve power provision (“clustering”). The algorithm aims at improving the efficiency and is able to reduce both the charging and the discharging losses by more than 10 percentage points. In addition it balances the states of charge of the individual storages and increases the self-consumption of PV-power of the households. These results are derived from detailed simulations of the system.
Keywords: frequency containment reserve power; virtual battery energy storage; clustering; efficiency; photovoltaic self-consumption

Integration of battery storage into the German electrical power system - Steber, David (it - Information Technology, 2016)
Keywords: The further integration of storage into the electric power system is unavoidable regarding the still increasing share of renewables and current market developments. Therefore a lot of different storage technologies are available today. The presented PhD-Thesis project will focus on integrating battery storage to the power system under different system and market conditions. Therefore; coupled control algorithms for single and virtual battery storage systems have to be developed depending on the battery's scope. For analyzing the reliability of different battery's scopes; the developed models will be integrated into an electric power system model for studying their influence on the power system and market concerning different development scenarios (renewables; nuclear phase-out). First actions dealt with the provision of Frequency Containment Reserve (FCR) power by a virtual battery storage under certain conditions in Germany. First results show appropriate working of implemented control algorithms and reliability for different shareholders.

Integration of Decentralized Battery Energy Storage Systems into the German Electrical Power System - Steber, David (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)

KOSiNeK - Kombinierte Optimierung, Simulation und Netzanalyse des elektrischen Energiesystems Deutschlands im europäischen Kontext - Projektvorstellung und erste Ergebnisse - Steber, David; Seifert, Gaby; Thurner, Christoph; Pruckner, Marco; Luther, Matthias; Martin, Alexander; German, Reinhard (VDI-Berichte 2303, 2017)

Simulation dezentraler vernetzter Speicher mit Teilnahme am Regelleistungsmarkt - Steber, David; Bazan, Peter; German, Reinhard (Bayern Innovativ Cluster Treff Cluster-Treff - Systemintegration dezentraler Batteriespeicher - Ergebnisse aus dem Modellprojekt SWARM, 2016)

SWARM – Different strategies and first experiences of providing frequency containment reserve power with distributed battery energy storage systems - Steber, David; Bazan, Peter; German, Reinhard (Integration of Sustainable Energy Conference (ISEneC) 2016, 2016)

SWARM - Erbringung von 1 MW Primärregelleistung mit verteilten Batteriespeichern in Haushalten - Steber, David; German, Reinhard (SMART GRIDS WEEK, 2016)

SWARM - Increasing Households’ Internal PV Consumption and Offering Primary Control Power with Distributed Batteries - Steber, David; Bazan, Peter; German, Reinhard (Energy Informatics - 4th D-A-CH Conference, EI 2015, Karlsruhe, Germany, November 12-13, 2015, Proceedings, 2015)
This Research in Progress Paper deals with a simulation approach for a virtual mass storage composed of small distributed battery energy storage units, installed in households with a roof-top photovoltaic system. On the one hand the household’s internal consumption of photovoltaic energy is maximized and on the other hand primary control reserve power is provided by a central storage controller. This concept is academically approved and rolled out in the field within this project. First simulation results show a household’s benefit of installing a battery energy storage system and an accurate working of the implemented virtual mass storag
UnivIS-Import:2015-11-17:Pub.2015.tech.IMMD.IMMD7.swarmi
Keywords: central controlled distributed batteries; internal PV consumption; frequency containment reserve power

SWARM – Primärregelleistungserbringung mit verteilten Batteriespeichern in Haushalten - Steber, David; Bazan, Peter; German, Reinhard (14. Symposium Energieinnovation 2016, 2016)

SWARM - Providing 1 MW PCR Power with Residential PV-Battery Energy Storage - Simulation and Empiric Validation - Steber, David; Pruckner, Marco; Bazan, Peter; German, Reinhard (IEEE PowerTech 2017, 2017)

SWARM - Strategies for Providing Primary Control Power with Distributed Battery Storage Systems - Steber, David; Bazan, Peter; German, Reinhard (IEEE EnergyCon 2016, 2016)

SWARM – Successful Provision of Frequency Containment Reserve with Distibuted Energy Storage Systems - Leepa, Claudia; Kufner, Annika; Mehl, Simon; Steber, David; Veerashekar, Kishan; Sigert, Ingo; Götz, Kornelia; German, Reinhard; Grimm, Veronika; Luther, Matthias (Conference Presentations and Materials of the "10th International Renewable Energy Storage Conference" (IRES 2016), Düsseldorf/Germany, 15-17 March 2015, 2016)
In July 2015, a network of 65 virtually connected distributed energy storage systems (ESS) with a total nominal power of 1 MW – so-called SWARM – was successfully prequalified for frequency containment reserve (FCR) provision within the balancing area of TenneT TSO GmbH in Germany. ESS were installed in private households possessing a rooftop photovoltaic system. In contrast to ordinary ESS available in the market for home application, SWARM-ESS do not only increase the households’ self-consumption, but they work as a virtual mass storage. Coordinated by an automated control center, SWARM is able to provide FCR by responding proportionally to frequency deviations of up to 200 mHz within few seconds and thus, contributes to stabilizing the grid. Hence, SWARM represents a systematic decentralized approach for meeting one of the main challenges of the energy transition in Germany. Roll out and operation of SWARM are conducted by a cooperation between N-ERGIE Aktiengesellschaft and Caterva GmbH. The project’s research activities are supported by groups of the Friedrich-Alexander-University addressing both, economic and technical issues. From an economic perspective, the identification of determinants of individual decision-making in exposure to novel technology is emphasized. As far as technical issues are concerned, the effects of distributed ESS on the grid, the provision of FCR by a virtual mass storage as well as the operational behavior of SWARM are analyzed. To this end, a stochastic and hybrid simulation model is developed to generate time series of all power flows within each house as well as the FCR provided. These time series are used for load flow calculations to identify the influence of ESS on the local distribution grid. All in all, this paper gives an overview of first experiences in the operation of SWARM as well as of research results from the different discipline
Keywords: distributed battery energy storage systems; frequency containment reserve

Virtueller Großspeicher zur Erbringung von Primärregelleistung – Pilotprojekt SWARM - German, Reinhard; Götz, Kornelia; Grimm, Veronika; Kufner, Annika; Leepa, Claudia; Luther, Matthias; Mehl, Simon; Sigert, Ingo; Steber, David; Veerashekar, Kishan (OTTI-Konferenz „Zukünftige Stromnetze für Erneuerbare Energien“, 2017)
Keywords: Virtueller Großsspeicher; dezentral; vernetzt; Primärregelleistung